Fenomena: Oversharing di Media Social dan Implikasinya Terhadap Kesadaran Privasi Mahasiswa - Mutiara Mutiara; Kanzilla Ayu Pracia; Anisa Pitriani; Darmawati Darmawati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Amid the rapid growth of social media, the phenomenon of oversharing has become an integral part of students’ daily lives. This raises an important question: are students able to go through their daily activities without engaging in oversharing? Platforms such as Instagram and TikTok are no longer merely tools for communication and information exchange, but also serve as spaces where students can freely express themselves. This study aims to explore how oversharing behavior occurs and examine its implications for students’ privacy awareness at UIN Suska Riau. Using a qualitative approach with a phenomenological method, data were collected through in-depth interviews and observations of students’ social media activities.The findings reveal that oversharing is driven by the need for social validation, the desire to express emotions, and a perceived sense of safety, particularly when using second accounts. However, behind this sense of freedom and security, there are often overlooked risks, such as information leakage, interpersonal conflicts, and digital threats. Therefore, enhancing privacy awareness is essential. Efforts such as digital litera cy education, strengthening self-control, and improving understanding of boundaries in sharing information must be continuously developed to help students use social media more responsibly.